A leitura de textos literários nas aulas de língua inglesa: desencontros entre teoria e prática - Ataide, Dayse Paulino de (2015)
It is certainly known that researching the importance of Literature in individuals’ educational training is a relevant topic in the language teaching area. This work aims to analyze the role of reading literary texts in high school English classes in Paraná public schools. A bibliographical review of theories which approach Literature as an important ally in individual development as well as in English teaching is done in order to perceive the obstacles which justify the discrepancy in the index of literary reading in relation to a foreign language. A questionnaire designed for high school English teachers in Paraná public schools is also accessed and interpreted. The purpose is to enhance some factors that lead to dislocation between theory and practice, language and Literature. Moreover, a didactical proposal is presented as an attempt to offer an alternative to promote the union of both language and Literature in the learning-teaching in English process.